Adipose-derived stem cells (ASCs) culture in spinner flask: improving the parameters of culture in a microcarrier-based system - Simão, Vinícius Augusto; Brand, Heloisa [UNESP]; da Silveira-Antunes, Roseli Nunes; Fukasawa, Josianne Thomazini; Leme, Jaci; Tonso, Aldo; Ribeiro-Paes, João Tadeu [UNESP] (Springer Nature, 2023)
Prior to clinical use, extensive in vitro proliferation of human adipose-derived stem cells (ASCs) is required. Among the current options, spinner-type stirred flasks, which use microcarriers to increase the yield of adherent cells, are recommended. Here, we propose a methodology for ASCs proliferation through cell suspension culture using Cultispher-S® microcarriers (MC) under agitation in a spinner flask, with the aim of establishing a system that reconciles the efficiency of cell yield with high viability of the culture during two distinct phases: seeding and proliferation. The results showed that cell adhesion was potentiated under intermittent stirring at 70 rpm in the presence of 10% FBS for an initial cell concentration of 2.4 × 104 cells/mL in the initial 24 h of cultivation. In the proliferation phase, kinetic analysis showed that cell growth was higher under continuous agitation at 50 rpm with a culture medium renewal regime of 50% every 72 h, which was sufficient to maintain the culture at optimal levels of nutrients and metabolites for up to nine days of cultivation, representing an 11.1-fold increase and a maximum cell productivity of 422 cells/mL/h (1.0 × 105 viable cells/mL). ASCs maintained the immunophenotypic characteristics and mesodermal differentiation potential of both cell lines from different donors. The established protocol represents a more efficient and cost-effective method to obtain a high proliferation rate of ASCs in a microcarrier-based system, which is necessary for large-scale use in cell therapy, highlighting that the manipulation of critical parameters optimizes the ASCs production process.
Keywords: Adipose tissue; Cell proliferation; Cultispher-S® microcarrier; Human mesenchymal stem stromal cells; Kinetic analysis; Spinner flask; Suspension culture